The Role of UKT Scholarships in Moderating Student Financial Attitudes and Financial Literacy on Finance Management Behavior - Khairatun Nazah; Ayu Wirda Ningsih; Rudy Irwansyah; Dewi Rafiah Pakpahan; Septa Diana Nabella (Institute of Computer Science (IOCS), 2022)
The problem in the research is the management behavior of students who receive UKT scholarships, especially students who cannot afford them and students who work. Indeed, in principle, the UKT scholarship is directly deducted from the cost of education. However, some students who get the scholarship have consumptive behavior such as buying a new cellphone and taking vacations. This study aims to determine the role of UKT scholarships in moderating financial attitudes and financial literacy on financial management behavior. This type of research is quantitative. The method of analysis in this study is a linear regression with a moderating model. The population in this study was 81 students who received UKT scholarships in 2021. The sampling technique used a saturated sample. So 81 students were sampled. The results of the study indicate that financial attitudes do not affect finance management behavior. Financial literacy has a positive and significant effect on finance management behavior. Finally, UKT scholarships have a role in strengthening or improving financial attitudes towards finance management behavior. Meanwhile, UKT scholarships have a role in weakening or reducing financial attitudes towards finance management behavior.